An overview of the past decade of bufalin in the treatment of refractory and drug-resistant cancers: current status, challenges, and future perspectives - Ye, Qingmei; Zhou, Xin; Ren, Han; Han, Fangxuan; Lin, Rong; Li, Juan (Frontiers in Pharmacology, 2023)
Profound progress has been made in cancer treatment in the past three decades. However, drug resistance remains prevalent and a critical challenge. Drug resistance can be attributed to oncogenes mutations, activated defensive mechanisms, ATP-bind cassette transporters overexpression, cancer stem cells, etc. Chinese traditional medicine toad venom has been used for centuries for different diseases, including resistant cancers. Bufalin is one of the bufadienolides in toad venom that has been extensively studied for its potential in refractory and drug-resistant cancer treatments in vitro and in vivo. In this work, we would like to critically review the progress made in the past decade (2013-2022) of bufalin in overcoming drug resistance in cancers. Generally, bufalin shows high potential in killing certain refractory and resistant cancer cells via multiple mechanisms. More importantly, bufalin can work as a chemo-sensitizer that enhances the sensitivity of certain conventional and targeted therapies at low concentrations. In addition, the development of bufalin derivatives was also briefly summarized and discussed. We also analyzed the obstacles and challenges and provided possible solutions for future perspectives. We hope that the collective information may help evoke more effort for more in-depth studies and evaluation of bufalin in both lab and possible clinical trials.